MnO2 Nanoflowers Induce Immunogenic Cell Death under Nutrient Deprivation: Enabling an Orchestrated Cancer Starvation‐Immunotherapy - Yannan Yang; Zhengying Gu; Jie Tang; Min Zhang; Yang Yang; Hao Song; Chengzhong Yu (Advanced Science, 2021)
Abstract MnO2 nanoparticles have been widely employed in cancer immunotherapy, playing a subsidiary role in assisting immunostimulatory drugs by improving their pharmacokinetics and/or creating a favorable microenvironment. Here, the stereotype of the subsidiary role of MnO2 nanoparticles in cancer immunotherapy is challenged. This study unravels an intrinsic immunomodulatory property of MnO2 nanoparticles as a unique nutrient‐responsive immunogenic cell death (ICD) inducer, capable of directly modulating immunosurveillance toward tumor cells. MnO2 nanoflowers (MNFs) constructed via a one pot self‐assembly approach selectively induce ICD to nutrient‐deprived but not nutrient‐replete cancer cells, which is confirmed by the upregulated damage associated molecular patterns in vitro and a prophylactic vaccination in vivo. The underlying mechanism of the MNFs‐mediated selective ICD induction is likely associated with the concurrently upregulated oxidative stress and autophagy. Built on their unique immunomodulatory properties, an innovative nanomaterials orchestrated cancer starvation‐immunotherapy is successfully developed, which is realized by the in situ vaccination with MNFs and vascular disrupting agents that cut off intratumoral nutrient supply, eliciting potent efficacy for suppressing local and distant tumors. These findings open up a new avenue toward biomedical applications of MnO2 materials, enabling an innovative therapeutics paradigm with great clinical significance.